Functional and structural characterization of the proteins from early steps of calicheamicin biosynthesis - Kong, Rong (2011)
Polyketides are structurally diverse secondary metabolites produced by bacteria, fungi and plants with a vast variety of biological activities and pharmaceutical properties. Among the polyketide products, naturally-occurring enediynes are some of the most potent antitumor natural products ever discovered. There are two different types of enediyne cores known to date, namely the bicyclo[7.3.0]-dodecadienediyne and bicyclo[7.3.1]-tridecadiynene. Despite some variations in structure, all enediynes consist of three important functional moieties that account for their unprecedented antibiotic and antitumor activities. A central aglycone warhead “attacks” DNA by hydrogen abstraction through the free radicals generated by the Bergman or Myers-Saito cyclization mechanism; a delivery system composed of oligosaccharide fragments guides the molecule to the DNA target and a triggering device activates the molecule to generate the highly reactive free radicals. Due to their astonishing capacity in cleaving DNA, some of the enediynes have already been employed in cancer treatment.